Mechanisms for the formation of communicative behavior in the work with students with autism spectrum disorders - Sunko T.Yu (Moscow State University of Psychology and Education, 2017)
The problem of the formation of communicative behavior in students with autism spectrum disorder in considered. The communicative norms are described on the basis of which speech communication is founded. The mechanisms of constructing of communicative behavior in work with students with autism spectrum disorders within the framework of the lesson and after-hour activities are defined.